2012
DOI: 10.21608/jppp.2012.84089
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF POTENTIAL ALLELOPATHIC EGYPTIAN RICE CULTIVARS AGAINST Echinochloa crus-galli AND Echinochloa colonum

Abstract: With the burgeoning population of the world, achieving the food security has become a challenge to mankind; as a result only yield maximization is becoming the last word of modern agriculture. Although this approach is satisfying the food demand to almost a desirable extent, but is directly and indirectly causing negative impact on quality of the product, environment and overall human health. This system is mostly based on the use of heavy doses of herbicides to control weeds. Therefore, these experiments were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Some reports have shown that Japonica rice cultivars have higher allelopathic potential than Indica rice varieties [ 26 ]. Nevertheless, both Koshihikari and Jasmine cultivars have been demonstrated to be allelopathic varieties [ 27 ]. In addition, Xuan et al [ 28 ] reported Japonica rice varieties show more abiotic tolerance than Indica rice.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports have shown that Japonica rice cultivars have higher allelopathic potential than Indica rice varieties [ 26 ]. Nevertheless, both Koshihikari and Jasmine cultivars have been demonstrated to be allelopathic varieties [ 27 ]. In addition, Xuan et al [ 28 ] reported Japonica rice varieties show more abiotic tolerance than Indica rice.…”
Section: Discussionmentioning
confidence: 99%
“…However, instead of developing new competitive genotypes, allelopathy can be more useful to screen the existing germplasm for allelopathic crop genotypes [18]. It was shown that some rice cultivars were able to suppress the growth of various paddy common weeds, including the Echinochloa species that cause severe yield losses, showing greater allelopathic potential than others [19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%